Compostos bioativos e atividade sequestrante de radicais livres de quatro cultivares do Coffea arabica L. em diferentes estádios de maturação dos frutos - Costa, Mariana de Campos da [UNESP] (2015)
Among the most consumed bebibas in Brazil stands out for coffee, a grain belonging to the Rubiaceae family, genus Coffea. Brazil produced in 2014, 45,3milhões bags of coffee. Brazilian exports reached approximately 33.36 million bags, with the US 5.98 billion revenue. Several factors may influence the quality of the beverage, as the variety, growing conditions, ripening of fruits, factors pre and post-harvest, drying, roasting of the beans among others, also the coffee has in its bioactive composition as phenolic acids, caffeine and trigonelline, which may help prevent some diseases. The objective of this study was to quantify the phenolic content and total flavonoids, antioxidant activity, caffeine and phenolic acids composition of four cultivars of Coffea arabica (Acaiá, Obatã, Catuaí Yellow Catuaí Red) during fruit maturation stages (green, green-cane, cherry and passes) and pulped. Antioxidant activity was measured by the reduction method of DPPH and ABTS radicals; total phenolics by the Folin-Ciocalteu method; and the total flavonoids by colorimetric reaction with aluminum chloride. Phenolic acids (chlorogenic acid, trigonelline and ferulic acid) were separated and quantified by HPLC with diode array detector and a C18 column. The cultivars Catuaí Yellow and Catuaí Red showed the highest levels of total phenolic compounds and total flavonoids. The Acaiá and Obatã cultivars had higher caffeine content. Regarding the chlorogenic acid, higher concentrations were observed in Acaiá and Catuaí Red cultivars and most ácifo ferulic content in Catuaí Yellow. Higher antioxidant activity was found in Acaiá and lower in Obatã. With the ripening of fruits there is a decrease in caffeine concentration. Highest antioxidant activity of coffee fruit is due to the content of chlorogenic acid.